Sustainable Project Management In Renewable Energy Development In Indonesia - Muhammad Hijerah Al Ahmad; Muslika (Daengku: Journal of Humanities and Social Sciences Innovation, 2025)
This study aims to analyze the effect of sustainable project management practices on the success of renewable energy projects in Indonesia, placing stakeholder engagement and green risk management as explanatory factors that reinforce the stability of project implementation. The approach used is an explanatory quantitative method with a cross-sectional design. Data were collected through a Likert-scale questionnaire survey of renewable energy project practitioners in Indonesia who were directly involved in project planning, execution, and control. Instrument testing showed that all constructs met the criteria for validity and reliability, making them suitable for inferential analysis. The analysis was performed using multiple linear regression after the classical assumption tests were satisfied. The results indicate that sustainable project management practices have a significant positive effect on project success and are the strongest predictor compared to other variables. Furthermore, stakeholder engagement and green risk management were also found to have significant positive effects on project success, indicating that multi-actor coordination and the mitigation of regulatory social environmental risks are key to keeping projects on track with regard to cost, time, quality, and public acceptance. These findings affirm that improving renewable energy project performance should not focus solely on technical aspects but requires strengthening sustainability governance, structured engagement strategies, and adaptive risk management systems.